An unusual homicidal stab wound of the cervical spinal cord: A single case examined by post-mortem computed tomography angiography (PMCTA). (September 2015) - Savall, Frederic; Dedouit, Fabrice; Mokrane, Fatima-Zohra; Rougé, Daniel; Saint-Martin, Pauline; Telmon, Norbert
Highlights: We report the case of a woman killed by her boyfriend with a chef's knife. We noted complete section of the spinal cord and section of cervical vessels. Cases of spinal cord injuries secondary to stab wounds are rare in the literature. We illustrate the value of Post-Mortem Computed Tomography Angiography, which is useful for the detection of injured vessels. Abstract: We report an unusual case of homicidal stab wound of the cervical spinal cord, which illustrates the value of post-mortem computed tomography angiography (PMCTA) in cases of vascular injury. First, we noted a posterior and horizontal trajectory to the neck with complete section of the cervical spinal cord between the first and second cervical vertebrae. This lesion was accompanied by section of the right vertebral and right deep cervical arteries. We also noted an anterior cervical trajectory with an injury to the right internal jugular vein and an anterior right chest wound with a lung trajectory and section of the internal mammary vessels. Cases of spinal cord injuries secondary to stab wounds are rare in the literature. Only one large series has been published from Cape Town. Complete section of the cervical spinal cord accounts for only 4.5% of all cases. Furthermore, lethal cases are rare and classically victims survive and present neurological sequelae. We found only one similar case but despite the transection of the cervical spinal cord the patient survived. Some studies suggest that PMCTA may be very helpful in visualizing vascular system injuries. Our observations are consistent with this proposal. The use of different-time acquisitions was essential for detection of the injured vessels.